(NsEJSMOAKUSTI^ESKIE ISSLEDOWANIQ PEREHODNYH ZON (B/s - (NsELIWERSTOW(B, (NnIKOLAJ iWANOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 109-112 (87 (NNAZW(B.)s
Keywords: (NaKUSTI^ESKIJ METODs; (NgEOLOGIQs; (NsEJSMI^ESKIE NABL@DENIQ MORSKIEs